Pengaruh Transformasi Ekonomi Digital Untuk Meningkatkan Produktivitas Dan Daya Saing UMKM Di Indonesia - Sari Gulo, Rilda Purnama; Faundri, Ranazah Aqila Faundri; Nurhaliza, Suchi; Dwi Prayoga, Muhammad Lexi Sorta; Idayati, Irma; Fadly, Muhammad; Ferdinand, Ahmad (Jurnal Serambi Ekonomi dan Bisnis, 2024)
In the information age, Micro, Small and Medium Enterprises (MSMEs) have many opportunities to improve their productivity and competitiveness. Many small and medium enterprieses in Indonesia. Are still not using digital technology. Digital technology allows MSMEs to automate manual processes, reduce operational costs, and expand market reach. To improve the produkctivity and efficiency of micro, small, and medium sized businesses digital transformation has become crucial. Digitalization of business processes, use of management software, and use of e-commerce platforms are some examples of digital technologies